Teacher’s Perspectives: Learning Interest of the Fourth Grade Students in State Elementary School 2 Bunder during the COVID-19 Pandemic - Zulfan Hanif Rahman; E. Kus Eddy Sartono; Reni Setyaningsih (AL-ISHLAH: Jurnal Pendidikan, 2022)
The COVID-19 pandemic has affected the education sector. This can be seen in the shift in the education system from offline to online learning at all levels of education. Elementary schools are one of the educational institutions that implement the online learning system. Indeed, this affects the student's learning interests as they are required to learn from home. This study used the qualitative description method. This study aims to identify the student's learning interests during the implementation of online learning. The results of the study showed that the students tended to have lower learning interests during the pandemic. This condition was influenced by boredom and a lack of monitoring from teachers and parents during the learning process.